Activation of CD40 with platelet derived CD154 promotes reactive oxygen species dependent death of human hepatocytes during hypoxia and reoxygenation. - Ricky H Bhogal (Public Library of Science (PLoS), 2012)
Background Hypoxia and hypoxia-reoxygenation (H-R) are pathogenic factors in many liver diseases that lead to hepatocyte death as a result of reactive oxygen species (ROS) accumulation. The tumor necrosis factor super-family member CD154 can also induce hepatocyte apoptosis via activation of its receptor CD40 and induction of autocrine/paracrine Fas Ligand/CD178 but the relationship between CD40 activation, ROS generation and apoptosis is poorly understood. We hypothesised that CD40 activation and ROS accumulation act synergistically to drive human hepatocyte apoptosis. Methods Human hepatocytes were isolated from liver tissue and exposed to an in vitro model of hypoxia and H-R in the presence or absence of CD154 and/or various inhibitors. Hepatocyte ROS production, apoptosis and necrosis were determined by labelling cells with 2',7'-dichlorofluorescin, Annexin-V and 7-AAD respectively in a three-colour reporter flow cytometry assay. Results Exposure of human hepatocytes to recombinant CD154 or platelet-derived soluble CD154 augments ROS accumulation during H-R resulting in NADPH oxidase-dependent apoptosis and necrosis. The inhibition of c-Jun N-terminal Kinase and p38 attenuated CD154-mediated apoptosis but not necrosis. Conclusions CD154-mediated apoptosis of hepatocytes involves ROS generation that is amplified during hypoxia-reoxygenation. This finding provides a molecular mechanism to explain the role of platelets in hepatocyte death during ischemia-reperfusion injury.